2017
DOI: 10.1063/1.4996618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen-accommodation ability of electrodes in SiNx-based resistive switching devices

Abstract: Nitrides could create opportunities of tuning resistive-switching (RS) characteristics due to their different electrical properties and ionic chemistry with oxides. Here, we reported on the effect of nitrogen-accommodation ability of electrodes in SiNx-based RS devices. The Ti/SiNx/Pt devices show a self-compliance bipolar RS with excellent reliability. The W/SiNx/Pt devices provide an unstable RS and fall to an intermediate resistance state (IRS) after a set process. The low resistance states of the Ti/SiNx/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The Si‐DBs have three main sources: the initial ones, those formed by removing the nitrogen from Si‐N bonds, and those formed by removing the hydrogen from SiH bonds. It is possible to break the SiN and the SiH bonds by the collision of the electrons, which are accelerated by the electric field . The produced Si‐DBs and the initial defects constitute conductive channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Si‐DBs have three main sources: the initial ones, those formed by removing the nitrogen from Si‐N bonds, and those formed by removing the hydrogen from SiH bonds. It is possible to break the SiN and the SiH bonds by the collision of the electrons, which are accelerated by the electric field . The produced Si‐DBs and the initial defects constitute conductive channels.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the analysis results of the Sample C. The HRS of the device obeys the Schottky emission, which is a field‐assisted thermionic emission over a surface barrier; while the LRS of the device obeys the Ohmic conduction. The equation of Schottky emission is: JSE=4πqm*k2h3T2exp[q(normalΦBqE/4πϵ0kr)kT] where J SE , and E are the current density of Schottky emission and the electric field, respectively, T , Φ B , q , k r , ϵ 0 , k , m* , and h are the absolute temperature, the Schottky barrier height, the electronic charge, the relative permittivity of the insulator, the vacuum permittivity, the Boltzmann's constant, the electron effective mass, and the Planck's constant, respectively. The Schottky barrier height can be deduced from the intercept of the ln(I) versus V 1/2 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, transistors which are connected to RRAM cells cannot endure such a high voltage and may cause problems of devices size scaling. [28] We found that tantalum has great nitrogenaccommodation ability to be the electrode. [15] But both of them are not perfect: the first one cannot ensure the position of generating defects thus the CCs have a random location and shape; the second one cannot ensure the quality of films and the initial defects are in a state of random distribution, the yield and reliability is not very good.…”
mentioning
confidence: 84%
“…[28] We found that tantalum has great nitrogenaccommodation ability to be the electrode. [28] We found that tantalum has great nitrogenaccommodation ability to be the electrode.…”
mentioning
confidence: 84%
See 1 more Smart Citation